2021
DOI: 10.5902/1980509829783
|View full text |Cite
|
Sign up to set email alerts
|

Produção de mudas de <i>Senegalia bahiensis</i> Benth. em diferentes volumes de tubetes

Abstract: Com o objetivo de definir qual o melhor volume de tubete e o tempo de permanência das mudas de Senegalia bahiensis em viveiro, foram instalados dois experimentos em delineamento inteiramente casualizado. No primeiro experimento, as mudas foram produzidas em três volumes de tubetes (55, 180 e 280 cm³), constituindo os tratamentos, quatro repetições e 49 mudas por repetição. No segundo experimento, foi realizada uma simulação de campo utilizando duas mudas por repetição, totalizando 24 mudas. As variáveis analis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
2
0
2
Order By: Relevance
“…Studies on container size for tree species allow us to infer that container sizes influence collar diameter, since the highest values are usually obtained in larger containers (Cunha et al, 2005;Ferraz & Engel, 2011;Freitas et al al., 2013;Freitas et al, 2021;Navroski et al, 2016;Pias et al, 2015), which corroborates the results found in this study (Table 1). According to Souza et al (2006), plants of the same species with a larger collar diameter have higher survival rates due to their capacity to form and grow new roots.…”
Section: Nursery Phasesupporting
confidence: 91%
“…Studies on container size for tree species allow us to infer that container sizes influence collar diameter, since the highest values are usually obtained in larger containers (Cunha et al, 2005;Ferraz & Engel, 2011;Freitas et al al., 2013;Freitas et al, 2021;Navroski et al, 2016;Pias et al, 2015), which corroborates the results found in this study (Table 1). According to Souza et al (2006), plants of the same species with a larger collar diameter have higher survival rates due to their capacity to form and grow new roots.…”
Section: Nursery Phasesupporting
confidence: 91%
“…2), emphasizing that this is the favorable volume to be adopted for the production of seedlings of this species. Other authors also reported that adopting containers with this volume benefits plant growth (Butzke et al 2018;Freitas et al 2021;Gasparin et al 2015). The results suggest that the smaller volume of the container limits the space for root expansion, in addition to reducing the availability of water, nutrients, and organic matter for seedling development, compromising their growth, both in the root axis and the aerial axis (Aguilar et al 2020;Cruz et al 2016;Dias et al 2016).…”
Section: Resultsmentioning
confidence: 90%
“…Usualmente, empresas do setor florestal utilizam a altura e o diâmetro do caule como critérios para selecionarem mudas apropriadas para uso em campo. São consideradas adequadas aquelas com altura entre 15 e 25 cm e DC com 2,5 mm (FREITAS et al, 2021). Em tese, os resultados encontrados neste estudo para as variáveis altura e DC para as mudas de H. courbaril estão em pleno acordo com os exigidos pelas empresas florestais.…”
Section: Resultsunclassified